PENANGANAN KASUS ANAK KORBAN PERCERAIAN ORANG TUA MELALUI PARENT CHILD INTERACTION THERAPY DI SAVE THE CHILDREN YOGYAKARTA - Ekmil Lana Dina (UIN Sunan Kalijaga Yogyakarta, 2018)
Intervention to be done is parent child interaction therapy, by coaching, providing effective skills between parents and children together. This intervention helps parents interact with parenting and mentoring techniques in children, including overcoming the case of children as victims of divorce parents who then dititipkan in orphanages. The objective of the study was to obtain a description and to analyze the characteristics of the subject of the implementation of parent child interaction therapy to the behavior, to the emotional state, and to the social situation of the child as the victim of divorce. The research used quantitative method with single subject design type or N = 1 with the ABA pattern model where the measurements will be performed in each period. As the purpose of the study to describe the effectiveness of the implementation of parent child interaction therapy in the handling of cases of child victims of divorce. The main hypothesis in this study is that H1 = parent child interaction therapy is effective in handling the AN subject as a divorce victim or H0 = parent child interaction therapy is not effective in handling the subject of AN as a divorce victim. The results show that parent child interaction therapy is effective for treating AN children as the victims of divorce, both in terms of behavior, emotions, and also the social subject of AN. Interactions built between the parents and the subject will continue to improve if both are committed to continuing to apply this therapy in their daily lives. Keywords: Divorce victim, Single subject experiment, Parent child interaction therapy